Date: Tue, 20 Jul 1999 07:51:48 -0600 (CST) Subject: differentiation
Name: nicholas
Question: Hi Nicholas
Since the tangent lines at x=1 and x=3 are parallel to the x-axis the derivative of the function is zero at x=1 and x=3. If ^{x} (p x^{2} + q x + r)^{x} (p x^{2} + (2p + q) x + (q + r))
Since f'(1) = 0 and f'(3) = 0, substituting x=1 and x=3 into f'(x) gives two equations in the variables p, q and r. (It is important here to remember tha e The final condition you have is that f(0) = 9 which gives a third equation in the variables p, q and r. Now you should be able to solve for these variables.
Cheers, To return to the previous page use your browser's back button. |